Accounting for Social and Environmental Sustainability: A Multi-Capital Approach (Routledge Studies in Accounting, 2025)
For a company, managing its social and environmental performance is no longer just a matter of reducing its impact; it must also be able to assess its contribution to resolving or aggravating social and environmental problems. This book argues that the current work on accounting for sustainability has not yet given organisations a tool to integrate their performance within the planetary and social framework that conveys actual "planetary and social budgets", and that business organisations lack the possibility to go beyond incremental performance measurement. It offers an in‑depth examination of multi‑capital accounting, which has already been integrated within the Corporate Sustainability Reporting Directive and will follow on from sustainability reporting. The LIFTS model (Limits and Foundations Towards Sustainability Accounting Model) used in this book combines various scientific and practical contributions to develop budgets for environmental impacts and social obligations on an organisational scale. It proposes an accounting mechanism that enables an organization to manage each of its budgets and measure variances between forecast and actual. It provides an introduction to the principles of this model and its conditions of application and describes its implementation in numerous companies. While the main audience for the book is academics, advanced students and researchers in accounting for sustainability, business and management and economics, it will also appeal to practitioners, policymakers, national standard setters, think tanks and non-governmental organizations (NGOs).